2(x+1)+(x+3)=3x-13

Simple and best practice solution for 2(x+1)+(x+3)=3x-13 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(x+1)+(x+3)=3x-13 equation:


2(x+1)+(x+3)=3x-13

We simplify the equation to the form, which is simple to understand
2(x+1)+(x+3)=3x-13

Reorder the terms in parentheses
+(+2x+2)+(x+3)=3x-13

Remove unnecessary parentheses
+2x+2+(+x+3+)=+3x-13

Remove unnecessary parentheses
+2x+2+x+3=+3x-13

We move all terms containing x to the left and all other terms to the right.
+2x+1x-3x=-13-2-3

We simplify left and right side of the equation.
0x=-18

0=-18

The left and right sides are not equal, therefore there is no solution. This equation is invalid.

See similar equations:

| 3+8x=3(2x-11) | | 3-4a=(a-3) | | x+5+x-3+x=x | | x+5+x-3x= | | 7++9= | | -[6z-(8z+1)]=1+(1z+2) | | 2(X-8)=X+17 | | -[6z-(8z+1)]=1t(1z+2) | | (10+1.50)-(6+1)= | | (8+w)(5w+7)=0 | | 8-2x+2=5x+3 | | 8-2x+2=5x | | -4(n-3)= | | 7(x+35)=273 | | 13/15+(8/15)= | | 8.28=5r | | -2(6+x)= | | 2(x+12)=3*x-31 | | (10j-7)-(9j+2)= | | 3x+22+5y+11=180 | | 5y+11=180 | | x-2+3=7 | | (63+5)+(72-3)= | | 8+5(x+3)+7x=x | | (7y+1)(3y-4v-2)= | | 2(4x+1)=42 | | 9+3m= | | (7t+5)+(8t-3)= | | 4x^3-3x^2+9=0 | | 4x-8=79+9x | | 2x+2u=5 | | 1/2(6x-10)+1/3(6+9x)= |

Equations solver categories